IMPLEMENTATION OF MARKETING STRATEGY PLANNING WITH BUSINESS MODEL CANVAS (BMC) IN MICRO, SMALL AND MEDIUM ENTERPRISES OF BAROKAH MULIA BUILDING SHOPS, KEDIRI REGENCY - Zeni Agustin, Khoirun Nisa'; Samari, Samari (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study is to improve business marketing strategies by implementing BMC in MSMEs of Barokah Mulia Building Stores in Kediri Regency. Design/Methode/Approach : This research uses a qualitative method. The data collection method was carried out through in-depth interviews, In data analysis, researchers used reduction and classification techniques to filter information relevant to the focus of the research. After the interview and observation, the data that has been collected will be grouped according to the interview themes conducted Research Finding : The results of the study show that Barokah Mulia Building Shop has a good and structured business model, and can meet the needs of customers in various segments. The main customers of the Barokah Mulia Building Shop are contractors, builders, and individuals who are building houses. Strong value proposition is offered in this store by providing a wide range of quality building materials, fast delivery services, as well as technical support and product consultation for customers. Through effective distribution channels, both through physical stores and delivery services, as well as good customer relationships, Toko Bangunan Barokah Mulia has resulted in building loyal and deep relationships with customers. Theoretical contribution/Originality : With this research, it is hoped that it can find out how Barokah Mulia Building Shop MSMEs can be helped in implementing more effective marketing strategies. In addition, it is hoped that this research can contribute to the planning of marketing strategies for the building MSME business model in Indonesia. Practitionel/Policy implication : For practitioners, the implementation of marketing strategy planning with the Business Model Canvas (BMC) can help micro, small and medium enterprises (MSMEs) owners to design and evaluate business models systematically and efficiently, as well as identify important elements such as customer segments, value propositions, and distribution channels that suit the needs of the local market. This allows for increased competitiveness and business sustainability. The results of this study can be the basis for formulating policies that support the implementation of BMC in the development of MSMEs, such as training or counseling programs on effective business planning and the use of digital technology tools, e-commerce platforms to improve the performance and competitiveness of MSMEs at the local and national levels. Research limitation : The main focus of this research is how to implement marketing strategy planning using Business Model Canvas (BMC) at Barokah Mulia Building Stores in Kediri Regency.